Passive fuel cell/lithium-ion capacitor hybridization for vehicular applications. (13th August 2021) - Macias, Alvaro; El Ghossein, Nagham; Trovão, João; Sari, Ali; Venet, Pascal; Boulon, Loïc
Abstract: Electric recreational vehicles represent a new challenge in terms of power supply systems compared to the current light-duty electric vehicles, which achieve high performance and long-range. The recreational vehicles need to heed the limited dimension requirements while assuring the high requested power. This paper proposes an integration of Lithium-Ion Capacitor (LIC) with Fuel Cell (FC) without any power electronic device for a three-wheel electric motorcycle. Unlike other hybrid power supply systems, the proposed FC-LIC passive configuration is lighter, compact, more efficient, and simpler to implement. Due to the different impedance of the components the system is self-management, in which FC supplies the average power component and LIC operates as a low-pass filter. In this respect, a simulator is built based on experimental tests to study the system performance in terms of hydrogen consumption and FC degradation. Subsequently, the system is tested under three standard motorcycle driving cycles at three different FC system lifespan stages. The obtained results demonstrate that a passive topology can supply the requested power along different FC stages of life and reported just an increment of 12% of hydrogen consumption at the oldest condition compared to the new condition. Graphical abstract: Image 1 Highlights: Integration of LIC technology with a fuel cell system for a recreational vehicle. Development of a hybrid FC-LIC vehicle simulator based on experimental data. The system is tested under standard driving cycles at different FC lifespan stages. The proposed passive design supplies the requested power under all the conditions. The passive FC-LIC topology is lighter, simpler to implement and self-management.